ANALISIS KADAR NITROGEN DIOKSIDA (NO2) DAN PARTICULATE MATTER 10 (PM10) UDARA AMBIEN DAN KELUHAN KESEHATAN PADA PEDAGANG KAKI LIMA DI SEPANJANG JALAN RAYA KELURAHAN LALANG KECAMATAN MEDAN SUNGGAL TAHUN 2014 - henny pradipta tarigan; surya dharma; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Main road is the road that connecting one region with another. Kelurahan Lalang Kecamatan Medan Sunggal road was the gateway for transportation that derived from Deli Serdang, Binjai, Langkat, and other cities to Medan. Transportation activities will generate positive impacts and negative impact. One of the negative impact is in form of air pollution. The research is aimed to know that levels of nitrogen dioxide ( NO2 ) and particulate matter ( PM10 ) air ambient and cadger health complaints along Kelurahan Lalang Kecamatan Medan Sunggal road in 2014. The type of research is descriptive. The sample in this research are 45 persons using proportional stratified random sampling. The result showed that the most respondents was 40 - 50 years ( 42,2 % ), most were gender female ( 55,6 % ), respondent who smoking ( 33.3 % ). Respondents has traded >10 years ( 64,4 % ) and respondents has traded < 12 hours per day ( 95.6 % ). Based on the measurement result, the highest levels is 40,97 µg/Nm3 for NO2 dan 121 µg/Nm3 for PM10. A number of 33 cadger who have complaints of the respiratory tract disorders and as much as 23 cadger who have complaints of eye irritation. The conclusion of this research is the level of NO2 and PM10 along Kelurahan Lalang Kecamatan Medan Sunggal road not exceeding from the limit of quality standards. Advised to cadger to use self protective when trading and put the plants that can absorb dust as preventive efforts. Keywords: main road, levels of NO2 and PM10, health complaints